Defining ovine dermal papilla cell markers and identifying key signaling pathways regulating its intrinsic properties - Wang, Shanhe; Hu, Tingyan; He, Mingliang; Gu, Yifei; Cao, Xiukai; Yuan, Zehu; Lv, Xiaoyang; Getachew, Tesfaye; Quan, Kai; Sun, Wei (Frontiers in Veterinary Science, 2023)
Dermal papilla cell (DPC), one of the key cell types during hair follicle development and regeneration, specifies hair size, shape and cycling. It is also an important in vitro screening model for hair growth. Although some characteristics of DPCs, such as agglutinative growth and marker genes, have been studied in mice and humans, the intrinsic properties of ovine DPCs and the regulatory mechanism of the intrinsic properties during continued culture in vitro remained unknown. In this study, based on our previous single-cell transcriptome sequencing on sheep lambskin, we verified SOX18 and PDGFRA as the novel marker genes of ovine DPCs through immunofluorescence staining on skin sections and cultured DPCs. Using continued cell culture and alkaline phosphatase staining, we found that different from mice and humans, ovine DPCs exhibit particularly robust and stable aggregation with unbated alkaline phosphatase activity till 30 passages during continued culture in vitro. Also, we found that the expression of some marker genes and the activity of Wnt/β-catenin signaling differ between early passaged DPCs and multiple passaged DPCs. Further, using Wnt/β-catenin agonist and antagonist, we demonstrated that Wnt/β-catenin signaling could regulate cell aggregation and alkaline phosphatase activity of ovine DPCs through regulating FGF and IGF signaling. This study provides the basis for isolating ovine DPCs and defines their intrinsic properties, which contribute to improving wool performance and medicine of hair regeneration.